2015
DOI: 10.1007/s11605-015-2915-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lymph Node Metastasis in Early Gastric Cancer with Signet Ring Cell Carcinoma

Abstract: Given the low risk of lymph node involvement, we recommend that endoscopic submucosal dissection be safely applied for early gastric signet ring cell carcinoma when tumor confined to mucosa, size ≤2 cm, and without lymphovascular invasion and ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…However, recent clinicopathology studies have shown contrasting evidence for intramucosal signet ring cell carcinoma that arises in the isthmus/neck of a gastric unit and is more common in young women, distal stomach with flat and depressed growth patterns [27,28,29,30,31]. A significantly better 5-year overall survival rate has been reported in patients with early signet ring cell carcinoma than in those with non-signet ring cell carcinoma at the same stage [32,33].…”
Section: Low Risk Of Nodal Metastasis For Intramucosal Signet Ring Cementioning
confidence: 99%
See 2 more Smart Citations
“…However, recent clinicopathology studies have shown contrasting evidence for intramucosal signet ring cell carcinoma that arises in the isthmus/neck of a gastric unit and is more common in young women, distal stomach with flat and depressed growth patterns [27,28,29,30,31]. A significantly better 5-year overall survival rate has been reported in patients with early signet ring cell carcinoma than in those with non-signet ring cell carcinoma at the same stage [32,33].…”
Section: Low Risk Of Nodal Metastasis For Intramucosal Signet Ring Cementioning
confidence: 99%
“…A significantly better 5-year overall survival rate has been reported in patients with early signet ring cell carcinoma than in those with non-signet ring cell carcinoma at the same stage [32,33]. Compared to well-differentiated intestinal-type early adenocarcinoma, intramucosal signet ring cell carcinoma has been found to have a similar incidence of submucosal spread, lymphovascular invasion, and nodal metastasis [30,31]. Since Hyung et al [27] reported a very low (1.6%, 3/185) rate of nodal metastasis for signet ring cell carcinoma at the pT1a stage, a number of studies have confirmed this finding (Table 1) [27,28,29,30,31,32,33,34,35,36,37,38,39].…”
Section: Low Risk Of Nodal Metastasis For Intramucosal Signet Ring Cementioning
confidence: 99%
See 1 more Smart Citation
“…Several variables associated with LNM have been reported previously, including sex, [20] depth of invasion, [7] macroscopic type, [8] tumor size, [9] and LVI. [6] In both this cohort and Japanese series, SRC histology tends to spread more superficially instead of invading deeply.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, endoscopic submucosal dissection (ESD) has been indicated for early gastric SRC to maintain the quality of life in East Asia. [6,9] However, most studies only focused on identifying predictive factors associated with LNM, and failed to provide a quantified risk of LNM for individuals. [610] Moreover, the clinical performance between different treatment strategies has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%